Generation and validation of novel conditional flox and inducible Cre alleles targeting fibroblast growth factor 18 (Fgf18). Issue 9 (22nd July 2019) - Hagan, Andrew S.; Boylan, Michael; Smith, Craig; Perez‐Santamarina, Estela; Kowalska, Karolina; Hung, Irene H.; Lewis, Renate M.; Hajihosseini, Mohammad K.; Lewandoski, Mark; Ornitz, David M.
Abstract: Background: Fibroblast growth factor 18 (FGF18) functions in the development of several tissues, including the lung, limb bud, palate, skeleton, central nervous system, and hair follicle. Mice containing a germline knockout of Fgf18 (Fgf18 −/− ) die shortly after birth. Postnatally, FGF18 is being evaluated for pathogenic roles in fibrosis and several types of cancer. The specific cell types that express FGF18 have been difficult to identify, and the function of FGF18 in postnatal development and tissue homeostasis has been hampered by the perinatal lethality of Fgf18 null mice. Results: We engineered a floxed allele of Fgf18 ( Fgf18 flox ) that allows conditional gene inactivation and a CreER T2 knockin allele ( Fgf18 CreERT2 ) that allows the precise identification of cells that express Fgf18 and their lineage. We validated the Fgf18 flox allele by targeting it in mesenchymal tissue and primary mesoderm during embryonic development, resulting in similar phenotypes to those observed in Fgf18 null mice. We also use the Fgf18 CreERT2 allele, in combination with a conditional fluorescent reporter to confirm known and identify new sites of Fgf18 expression. Conclusion: These alleles will be useful to investigate FGF18 function during organogenesis and tissue homeostasis, and to target specific cell lineages at embryonic and postnatal time points. Key Findings: Successful generation of a floxed allele of Fgf18 and a tamoxifen inducible Cre recombinase allele driven by the Fgf18 promoter. Recapitulation of the Fgf18 null skeletal deformities by conditionally targeting Fgf18 in the mesenchyme. Identification of known and new sites of Fgf18 expression in the embryo, postnatal and juvenile skeleton, postnatal and adult visceral organs, and in the adult brain.